Photocatalytic properties of Fe-doped ZnO electrospun nanofibers. Issue 16 (November 2018) - Liu, Liu; Liu, Zhiwei; Yang, Yixin; Geng, Mingqian; Zou, Yiming; Shahzad, M. Babar; Dai, Yuxiang; Qi, Yang
Abstract: Undoped and Fe-doped Zinc Oxide (ZnO) nanofibers were prepared by electrospinning method to investigate the effect of transition metal ion doping on the photocatalytic performance of ZnO. A variety of techniques were employed to characterize various properties of the fabricated nanofibers. It was realized that the crystallization of ZnO fibers was significantly improved by optimizing the sintering conditions. The results revealed that Fe-doping greatly improved the photocatalytic activity of ZnO owing to modified nanofibers morphology and the reduced optical bandgap. The ZnO nanofibers showed the optimum photocatalytic activity for 1.5% Fe-doping percentage which was attributed to the presence of maximum dopant ions in the ZnO matrix. The enhanced photocatalytic performance of ZnO could increase its scope of industrial and commercial applications.